Compactability and mechanical properties of cold recycled mixes prepared with different nominal maximum sizes of RAP. (11th July 2022) - Orosa, P.; Orozco, G.; Carret, J.C.; Carter, A.; Pérez, I.; Pasandín, A.R.
Highlights: CRM were prepared with RAP from different sources and NMS, using the same mix proportions. SGC and Marshall compactions with different compaction energies were used. Volumetric properties were analyzed as a function of the RAP and compaction method. Mechanical behavior was analyzed using stiffness modulus and failure behavior tests. RAP gradation and voids content showed a greater effect on the mechanical behavior. Abstract: The use of cold recycled asphalt mixtures (CRM) has been soaring during recent years. Reclaimed Asphalt Pavement (RAP) is the main component of CRM, and despite the numerous studies on CRM, the impact of different RAP types has not been deeply studied. This study compares the volumetric and several mechanical properties of CRM prepared with RAP from two different sources and with various nominal maximum sizes (NMS). The mix design was fixed, and specimens were prepared using gyratory and impact compactors. Densities were measured before and after accelerated curing. Stiffness of CRM was investigated with Indirect Tensile Stiffness Modulus, tension–compression, and dynamic tests. Additionally, the cracking behavior was evaluated with Indirect Tensile Strength and Semi-Circular Bending tests. The particle size distribution was a key factor in the compactability of the CRMs studied. Together with temperature, the most influential factor on the studied mechanical properties was the air void content, while the differences in NMS showed no clear trends.